TYPES OF INTERACTIVE METHODS IN TEACHING FOREIGN LANGUAGES IN PRIMARY SCHOOLS - Djurayeva, Madina (Журнал иностранных языков и лингвистики, 2021)
This article describes the process of teaching foreign language materials in primary school, the process of teaching didactic games, on this basis, the definition of the theoretical basis of the problems of interaction of principles and methods of teaching, the process of teaching interaction and management. It is also stated that there is a priority of modern education in the production of scientific and methodological recommendations.